Kommunikasie·aantekeninge oor die Suid-Afrikaanse verkiesing - IMLLEM DE KLERK (Communicare)
It is a review of the 1994 election in South Africa from a variety of perspectives. The negotiation process from 1990 until 1993 was embedded in the dynamics of negotiation communication. Critical remarks are made regarding voter education and the various other structures organisationally involved with the election. The following statements: that the process was carried by political expectations about the election and not so much by the administration and organisation thereof; that State information must be completely divorced from the political party in power; and that a law in respect of freedom of information is essential. The election campaign is discussed from the perspective of policy communication, political rhetoric, propaganda techniques, the advertising campaign and the way in which the media handled the election. The statement is made that the election results prove that it was a symbolic election a racial election and that theWillem de Klerk is Spesiale Professor verbonde aan die Department Kommunikasie aan die RAU en bekende politieke analis en kommentator.The political climate in the country changed from pessimism to optimism within days after the election, is briefly discussed. Issues expected to receive attention in political discourse over the next three years, are summarised.A few research themes and fields of application for Communication Science in the context of South African politics, are explored